Mouse Models of Liver Parenchyma Injuries and Regeneration - Du, Yuan; Zhang, Wencheng; Qiu, Hua; Xiao, Canjun; Shi, Jun; Reid, Lola M.; He, Zhiying (Frontiers in Cell and Developmental Biology, 2022)
Mice have genetic and physiological similarities with humans and a well-characterized genetic background that is easy to manipulate. Murine models have become the most favored, robust mammalian systems for experimental analyses of biological processes and disease conditions due to their low cost, rapid reproduction, a wealth of mouse strains with defined genetic conditions (both native ones as well as ones established experimentally), and high reproducibility with respect to that which can be done in experimental studies. In this review, we focus on murine models for liver, an organ with renown regenerative capacity and the organ most central to systemic, complex metabolic and physiological functions for mammalian hosts. Establishment of murine models has been achieved for all aspects of studies of normal liver, liver diseases, liver injuries, and regenerative repair mechanisms. We summarize key information on current mouse systems that partially model facets of clinical scenarios, particularly those associated with drug-induced acute or chronic liver injuries, dietary related non-alcoholic liver disease (NAFLD), hepatitis virus infectious chronic liver diseases, and autoimmune hepatitis (AIH). In addition, we also include mouse models that are suitable for studying liver cancers (e.g., hepatocellular carcinomas), the aging process (senescence, apoptosis), and various types of liver injuries and regenerative processes associated with them.